2023
DOI: 10.1186/s43897-023-00063-2
|View full text |Cite
|
Sign up to set email alerts
|

Small secreted peptides (SSPs) in tomato and their potential roles in drought stress response

Kexin Xu,
Dongdong Tian,
TingJin Wang
et al.

Abstract: Tomato (Solanum lycopersicum) is one of the most important vegetable crops in the world and abiotic stresses often cause serious problems in tomato production. It is thus important to identify new regulators in stress response and to devise new approaches to promote stress tolerance in tomato. Previous studies have shown that small secreted peptides (SSPs) are important signal molecules regulating plant growth and stress response by mediating intercellular communication. However, little is known about tomato S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…When plants experience salt stress, exacerbating cell damage leads to the release of AtPEP3, which in turn induces downstream signaling responses. However, the intricacies Research on CEP regulation of plant drought tolerance has been extensive, and studies in crops such as wheat and tomato have revealed the crucial role of CEP in enhancing plant drought tolerance [80]. Application of the TaCEP1D peptide on wheat leaves has been shown to improve drought resistance [81].…”
Section: The Role Of Small Peptides Under Salt Stress In Plantsmentioning
confidence: 99%
“…When plants experience salt stress, exacerbating cell damage leads to the release of AtPEP3, which in turn induces downstream signaling responses. However, the intricacies Research on CEP regulation of plant drought tolerance has been extensive, and studies in crops such as wheat and tomato have revealed the crucial role of CEP in enhancing plant drought tolerance [80]. Application of the TaCEP1D peptide on wheat leaves has been shown to improve drought resistance [81].…”
Section: The Role Of Small Peptides Under Salt Stress In Plantsmentioning
confidence: 99%
“…28 In tomatoes, treatments with the drought-induced SlCEPs (Solanum lycopersicum C-terminally encoded peptides), specifically SlCEP10 and SlCEP11b peptides, have been found to enhance drought resistance. 29 Moreover, sbt3.8 (subtilisin-like serine proteases 3.8) mutants exhibit compromised tolerance to drought and osmotic stress, which can be ameliorated with PSK (Phytosulfokine) peptide treatment. 30 In this study, we discovered that two CLE peptides, NtCLE2 and NtCLE3, from a Nicotiana tabacum can trigger stomatal closure in three solanaceous plants (Nicotiana tabacum, Capsicum annuum, and Solanum melongena).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the wild type, rice plants overexpressing OsDT11 ( drought tolerance 11 , which encodes a novel cysteine-rich peptide) exhibited significant reductions in water loss and stomatal density, while the concentration of ABA increased substantially . In tomatoes, treatments with the drought-induced SlCEPs (Solanum lycopersicum C-terminally encoded peptides), specifically SlCEP10 and SlCEP11b peptides, have been found to enhance drought resistance . Moreover, sbt3.8 ( subtilisin-like serine proteases 3.8 ) mutants exhibit compromised tolerance to drought and osmotic stress, which can be ameliorated with PSK (Phytosulfokine) peptide treatment …”
Section: Introductionmentioning
confidence: 99%
“…26 Therefore, a standardized pipeline has been established for screening potential SSPs for certain species, as has been applied in Arabidopsis thaliana and tomato plants. 3,27 Solanaceae is one of the most important plant families in horticulture, encompassing a multitude of vital crops and ornamental plants such as tobacco (Nicotiana tabacum), pepper (Capsicum annuum), and tomato (Solanum lycopersicum). 28 The first small peptide discovered in tomato plants, known as Sys, mediates long-distance immune responses through its receptor, systemin receptor 1 (SYR1).…”
Section: ■ Introductionmentioning
confidence: 99%